Colposcopic Evaluation of Visual Inspection with Acetic Acid Positive Cases of Unhealthy Cervix (Journal of Bangladesh College of Physicians and Surgeons, 2019)
Cervical cancer is the commonest form of cancer in women in virtually all developing countries1. It is the third most common cancer among women worldwide2. Almost 80% of cervical cancer occurs in developing countries. In developed nations, the figure for invasive cervical cancer are much lower due to adaptation of different screening tests1. All sexually active women are at risk of acquiring a Human Papilloma Virus (HPV) infection which may lead to cervical cancer in the future3. Cervical cancer is a preventable disease as the different screening, diagnostic and therapeutic procedures are effective. The screening procedures are VIA (Visual inspection of cervix with acetic acid), Pap’s smear and HPV DNA test. Colposcopy is the triage in screening, taking colpospoy directed biopsy as well as treatment of CIN such as cold coagulation, cryotherapy, and LEEP (Loop electro-surgical excision procedure)4. Objective: To study the role of Colposcopy in the evaluation VIA positive cases of unhealthy cervix, to localize the leisons to obtain the biopsies from the selected areas and detection of precancerous lesion of cervix for early management. Meterials and Methods: This was a prospective observational study done among 306 married women aged 18-65 years who had clinically unhealthy cervix attending the VIA and colposcopy clinic in Department of Obstetrics and Gynaecology of Sir Salimullah Medical College and Mitford Hospital from January 2015 to December 2016. All the patients were subjected to VIA test. Colposcopic evaluation done in VIA positive cases and the findings were noted. Colposcopy directed biopsy was taken from colposcopically suspected areas. Results: Out of 306 cases, 63 women had positive VIA tests and 233 women had negative VIA tests. Colposcopic evaluation were undertaken among 63 VIA positive cases. Colposcopy directed punch biopsy revealed that 28 (60.32%) cases had positive lesions like CIN or invasive carcinoma and 25 (39.68%) had neither CIN or invasive lesions . Among positive leisons about 30.16% had CINI, 1.59 % had CIN II, 0% had CIN III and 28.57% had invasive carcinoma. In this study sensitivity and specificity of colposcopy examination of VIA positive cases were found 94.74% and 56% respectively. Conclusion: It is evident that colposcopy plays a very important role in the evaluation of VIA positive cases of unhealthy cervix. So that early diagnosis and treatment of preinvasive and early invasive carcinoma of cervixis is possible. So wide use of colposcopy in screening program of Bangladesh speciallly in the VIA positive cases can reduce the many young women’s morbidity and mortality.J Bangladesh Coll Phys Surg 2019; 37(2): 60-65